Introduction to agricultural economics - Penson, John B. (Prentice Hall, 2002)
For Introduction to Agricultural Economics courses at the freshman/sophomore undergraduate level.This jargon-free text provides beginning agriculture students with a readable, systematic understanding of the basic concepts and issues in economics as they relate to the food and fiber industry-a major segment of the U.S. economy. Covering the entire scope of key economic principles and their application to the food and fiber system, it traces major microeconomic, macroeconomic, and global forces influencing the decisions of producers and consumers of food and fiber products, and focuses on the leading problems and issues confronting this important industry today.